2021
DOI: 10.1111/jcmm.16491
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐454‐mediated NEDD4‐2/TrkA/cAMP axis in heart failure: Mechanisms and cardioprotective implications

Abstract: The current study aimed to investigate the mechanism by which miR‐454 influences the progression of heart failure (HF) in relation to the neural precursor cell expressed, developmentally downregulated 4‐2 (NEDD4‐2)/tropomyosin receptor kinase A (TrkA)/cyclic adenosine 3',5'‐monophosphate (cAMP) axis. Sprague‐Dawley rats were used to establish a HF animal model via ligation of the left anterior descending branch of the coronary artery. The cardiomyocyte H9c2 cells were treated with H2O2 to stimulate oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…For instance, Nedd4‐2 has been shown to regulate OGG1 protein levels in response to DNA damage, which may have implications for DNA repair capacity (Hughes & Parsons, 2020). In a study investigating mechanisms of heart failure, it was found that oxidative stress down‐regulates the expression of Nedd4‐2 to impair TrkA ubiquitination, which in turn promotes cAMP signaling that modulates heart activity (Wang et al, 2021). In another study looking at the cellular response to oxidative stress, it was found that decreased Nedd4‐2 expression at the mRNA transcript level promotes stability of a protein called LATS1 which facilitates cell death in response to oxidative stress (Rajesh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Nedd4‐2 has been shown to regulate OGG1 protein levels in response to DNA damage, which may have implications for DNA repair capacity (Hughes & Parsons, 2020). In a study investigating mechanisms of heart failure, it was found that oxidative stress down‐regulates the expression of Nedd4‐2 to impair TrkA ubiquitination, which in turn promotes cAMP signaling that modulates heart activity (Wang et al, 2021). In another study looking at the cellular response to oxidative stress, it was found that decreased Nedd4‐2 expression at the mRNA transcript level promotes stability of a protein called LATS1 which facilitates cell death in response to oxidative stress (Rajesh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It was also confirmed that Nedd4l was significantly upregulated in the brain of rats with acute cerebral ischemia ( Kim et al, 2021 ) and might function in exacerbating the toxicity of accumulated excitatory transmitters out of the cells in ischemia through the regulation of the degradation of glutamate transporters ( Sopjani et al, 2010 ; Vina-Vilaseca and Sorkin, 2010 ). Moreover, Nedd4l was reported as regulated by miR-454 to induce a cardioprotective effect ( Wang Y. et al, 2021 ). Besides, Tpm1 has a potential association with cognitive impairments as it was reported as a potential biomarker of AD for its upregulation in the platelets of AD and MCI patients ( Reumiller et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The miR-454 activates the cAMP pathway through the Nedd4L/TrkA axis, which ultimately inhibits cardiomyocyte apoptosis and alleviates myocardial injury. Results from this landmark study thus suggest that targeting the Nedd4L/TrkA/cAMP pathway may be a potential novel promising option for the prevention and treatment of heart failure [ 118 ].…”
Section: Nedd4l and Hypertensionmentioning
confidence: 99%
“… [ 114 , 115 ] Heart failure The miR-454 activates the cAMP pathway through the NEDD4L/TrkA axis, which ultimately inhibits cardiomyocyte apoptosis and alleviates myocardial injury. [ 118 ] Arrhythmia Long QT syndrome SCN5A-p.Y1977N disrupts the common Nedd4L binding site (from PPxY to PPxN), thus prevents the process of ubiquitination. [ 135 , 136 ] (Studies imply that there is not much direct connection between Nedd4L and arrhythmia, and most of the arrhythmias are related to the gene SCN5A that encodes the sodium channel.…”
Section: Nedd4l and Hypertensionmentioning
confidence: 99%